Birthplace is a risk factor for exchange transfusion in outborn infants admitted for jaundice in Myanmar: a case-control study. (2nd May 2020) - Cavallin, Francesco; Trevisanuto, Daniele; Thein, Aye; Booth, Amanda; Arnolda, Gaston; Kumara, Danica; U, Phyu; Myint, Sandar; Moccia, Luciano
Abstract: Aim: To evaluate the role of pathway to admission for jaundice among the risk factors for exchange transfusion in outborn infants in a low resource setting. Methods: This retrospective case-control study (1:1 ratio) was carried out at the Yankin Children's Hospital in Yangon (Myanmar). All cases were neonates admitted for treatment of jaundice between March 2013 and February 2014 and who required an exchange transfusion. Each control was the next noncase neonate admitted for treatment of jaundice and treated with phototherapy. Infant characteristics, pathways of admission and clinically relevant factors for exchange transfusion were collected. Results: One hundred thirty-four cases and 134 controls were included in the study. Among cases, home was the most common place of birth while public hospital was the most frequent source of referral. Among controls, private/public hospitals were the commonest places of birth and referral. At multivariable analysis, homebirth was associated with increased likelihood of receiving exchange transfusion at admission (OR 3.30, 95% C.I. 1.31–8.56). Conclusion: Homebirth was an independent risk factor for exchange transfusion at admission for jaundice in a low-resource setting. Appropriate health education of pregnant women and traditional/home birth attendants may contribute to reduce the need for exchange transfusion in low-resource settings.